HPV infection and endometrial polyps: insights from a case-control study - Leila Nazari; Mansoureh Vahdat; Samaneh Rokhgireh; Shahla Chaichian; Abolfazl Mehdizadehkashi; Zahra Aminzade; Roya Derakhshan (BMC, 2024)
Abstract Background Endometrial polyps are common benign lesions characterized by localized overgrowths of endometrial tissue within the uterine cavity. The etiology and pathogenesis of these polyps remain unclear. Human papillomavirus (HPV) infection, known for its association with various genital tract conditions, has been investigated concerning endometrial polyps, although research in this area is limited. Methods A case-control study involving 62 premenopausal women was conducted, with endometrial polyp cases and control groups matched for age and BMI. Biopsy samples were collected for HPV testing using polymerase chain reaction (PCR). Clinical and demographic data were collected and analyzed for associations between HPV presence and endometrial polyps. Results Results showed a higher prevalence of HPV (all types) in cases (4, 12.9%) compared to controls (1, 3.2%), with low-risk HPV being the most prevalent genotype detected and HPV 16 tested positive in one case diagnosed with polyp. While no significant association was found between HPV infection and the presence of endometrial polyps, the study suggests a potential role for HPV in their development. Interestingly, HPV presence in endometrial polyps was unrelated to histopathological features, patients' age, or BMI. Conclusion This study provides insights into the potential involvement of HPV infection in the development of endometrial polyps. Despite no significant association found, the prevalence of HPV in these polyps suggests a possible contributory role. Further research with larger sample sizes and more robust methodologies is warranted to clarify this association and its clinical implications.